Consumers’ purchase intention of rapid COVID-19 tests - Cortez, Klender; Rodríguez-García, Martha del Pilar; Reich, Christian (Universidad ESAN. ESAN Ediciones, 2023)
Purpose: This research aims to analyse the variables related to the purchase intention of COVID-19 rapid tests in Monterrey, Mexico's metropolitan area. Design/methodology/approach: The chosen method was probit regression. The results show that purchase intention depends on the consumer's perceived value and the perception of having a potential contagion and/or presenting symptoms related to the virus. Regarding limitations, the sampling method used in this investigation is a nonprobabilistic convenience approach delivered through a digital platform, which may not be the first option in other contexts. Findings: The findings indicate that the probability of the purchase intention of rapid COVID tests increases when consumers perceive symptoms of the disease and when they have higher education or are female rather than concerning price or income, as suggested by classical demand theory. Research limitations/implications. Probabilistic sampling was impossible due to the difficulty of collecting surveys during the COVID-19 pandemic. Instead, a nonprobabilistic sample of a representative random selection of different zip codes from the responses received was considered. Originality/value: The originality of the paper is its contribution to consumer behaviour during the COVID-19 pandemic in a Latin American context.

Propósito: Esta investigación tiene como objetivo analizar las variables relacionadas con la intención de compra de pruebas rápidas COVID-19 en Monterrey, área metropolitana de México. Diseño/metodología/enfoque: El método elegido fue la regresión probit. Los resultados muestran que la intención de compra depende del valor percibido por el consumidor y de la percepción de tener un potencial contagio y/o presentar síntomas relacionados al virus. En cuanto a las limitaciones, el método de muestreo utilizado en esta investigación es un enfoque no probabilístico de conveniencia entregado a través de una plataforma digital, que puede no ser la primera opción en otros contextos. Hallazgos: Los hallazgos indican que la probabilidad de la intención de compra de pruebas rápidas de COVID aumenta cuando los consumidores perciben síntomas de la enfermedad y cuando tienen educación superior o son mujeres, en lugar de preocuparse por el precio o los ingresos, como sugiere la teoría clásica de la demanda. Limitaciones/implicaciones de la investigación: el muestreo probabilístico fue imposible debido a la dificultad de recopilar encuestas durante la pandemia de COVID-19. En cambio, se consideró una muestra no probabilística de una selección aleatoria representativa de diferentes códigos postales a partir de las respuestas recibidas. Originalidad/valor: La originalidad del artículo es su contribución al comportamiento del consumidor durante la pandemia de COVID-19 en un contexto latinoamericano.
Keywords: Rapid COVID-19 tests; Purchase intention; Pruebas rápidas COVID-19; Mexico; Intención de compra; Probit; México; Probit; Symptomatology; Sintomatología; https://purl.org/pe-repo/ocde/ford#5.02.04